Carcass characteristics of Sudan Desert sheep - Osman, A.H.; El-Shafei, S.A. (1967)
This report presents information on the carcass characteristics of Sudan Desert sheep, which constitute 65% of the Sudan sheep Population. A total of 35 yearling rams, purchased from the livestock market were slaughtered and their carcass evaluated. The warm dressing percentage ranged from 38.7% to 54.3% with an average of 42.8%. Dressing percentage depended on body development as was determined by age, management and breed. The overall quality of production reflected the standard of production attained under less than optimal animal feeding.